CRTP: learning model for integrating STEM competencies in pre-service biology teachers - Marlina, Reni; Suwono, Hadi; Ibrohim, Ibrohim; Yuenyong, Chokchai; Hamdani, Hamdani; Pamungkas, Rahmania (Journal of Education and Learning (EduLearn), 2025)
The development of education shows the importance of integrating science, technology, engineering, and mathematics (STEM) in schools and preparing teachers who are ready to implement STEM in the classroom. This study aims to describe prospective teachers' perceptions of STEM competencies through the collaborative reflective teaching practice (CRTP) model in micro teaching courses. The method used was qualitative using interview assessment and questionnaire of STEM perception. This study used an experimental design conducted with 3 activities (initial test, teaching practice, and final test). The initial test and final test used a STEM perception questionnaire. Teaching practice in the form of applying the CRTP model which consists of 4 stages, namely plan, simulation, implementation, and reflection. The results of the study describe that STEM competencies develop well with the CRTP model. The questionnaire results showed that 96.2% of respondents strongly agreed that the CRTP model had proven valid for developing STEM competencies of prospective biology teachers. This research contributes to educators who prioritize meaningful learning experiences for prospective biology teachers. The authors suggest that effective STEM competencies should incorporate five main components: i) reflection, ii) collaboration, iii) integration of interdependent STEM disciplines, iv) skills related to STEM disciplines, and v) integrative STEM teaching and learning.